Cuaderno de Casos 1 (2009)
Caso 1: Rayco Ltda./ Paola Alfonso, Catalina Montealegre, Johanna Valenzuela -- Caso 2: Aviatur./Mónica Ramírez R., Pedro Ramiro Alfonso, Rodolfo Arturo Hernández, Juan Carlos Quintero Díaz -- Caso 3: Club deportivo La Equidad./ Liliana Bautista Pinilla, Julian Andrés Correa, Oscar Mauricio Roa P., Liliana Cristina Rodríguez, Diego Andrés Venegas. -- Caso 4: Materiales de Colombia S.A./ José Alexander Cáceres, Andrés Felipe Rozo, Lina Abiantun Bouantun -- Caso 5: Yokomotor./ Juan Carlos Galeano, Gerardo Andrés Moyano, Jorge Arturo Morales, Diana Yamile Ariza -- Caso 6: Bluemarketing Ltda./ Yuli Paola Prieto, Lis Yojana Soto, Alix Adriana Triana G., Juliana Vargas -- Caso 7: Georgoplast Ltda./ Juan Gabriel Sánchez, Omar G.Díaz, Angela Rossana Moreno, María Victoria Olaya -- Caso 8. Arce Rojas Consultores & Cia.S.A./ Paola Andrea Silva E., Arley Barrera Rico, Camilo Eduardo Mosquera -- Caso 9. M&J Ltda./ Marisol Ducuara, Luis Alberto Padilla, Juan Camilo González Diana Benavides.